A methodology for making a three-coil wireless power transfer system more energy efficient than a two-coil counterpart for extended transfer distance - Zhong,WX; Zhang,C; Liu,X; Hui,SYR (IEEE Transactions on Power Electronics, 2015)
A new methodology for ensuring that a three-coil wireless power transfer system is more energy efficient than a two-coil counterpart is presented in this paper. The theoretical proof and the conditions for meeting the objective are derived and practically verified in a practical prototype. The key features of the magnetic design are to: 1) shift the current stress from the primary driving circuit to the relay resonator; and 2) generate a large relay current for maximizing magnetic coupling with the receiver coil for efficient power transfer. Consequently, the current rating and cost of the driving circuit can be reduced and the overall quality factor and system energy efficiency are improved. This approach utilizes the combined advantages of the maximum efficiency principle and the use of relay resonator to overcome the energy efficiency problem for applications with extended energy transfer distances.